Kebijakan Politik Nahdlatul Ulama mengenai Dasar Negara 1945-1984 - Anggi Muhammad Adha (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2020)
The article mainly examined on “Why did NU’s political attitude regarding the state foundation change?”. The results showed that NU’s view on the relationship between religion and the state had changed. At first, the NU prominent figures supported that the Indonesia state must be based on Islam but in the following years NU supported Pancasila as the country’s foundation. NU’s support for the states’ foundation that must be based on Islam which can be seen from NU figures who convened in the Constituent Assembly. In the Constituent Assembly, NU along with other Islamic factions tried hard to make the state based on Islam. But the proposal was rejected by other factions who wanted Pancasila to be the states’ foundation. The debate between state supporters based on Islam and supporters of Pancasila did not find common ground. Thus on July 5th 1959, President Soekarno issued a Presidential Decree to end the debate. In the 1980s President Soeharto issued a policy by making Pancasila the sole principle of organizations in Indonesia. At first NU rejected this policy, but in the end, NU accepted this policy. The reason for NU accepted the policy, was due to government pressure and also the birth of a new NU’s generation that differ from the previous one. The new generation emphasized pluralist life in Indonesia and aimed to make the state the guardian of all religions.